Development of a heavy ion beam probe diagnostic for HL-2A tokamak. (1st January 2023) - Fan, H.R.; Gao, L.T.; Liu, A.D.; Zhuang, G.; Ido, T.; Xu, M.; Huang, J.C.; Zhang, J.; Feng, C.Q.; Zhou, C.; Liu, H.; Nie, L.; et al.
Abstract: A heavy ion beam probe (HIBP) is being developed and tested on the HL-2A tokamak. To focus on the turbulence measurement in high beta scenarios with the toroidal magnetic field of 1.35 T, a 500 kV thallium beam is chosen and optimized. The locations of the injection and detection system are determined based on the probing beam trajectory calculations. The status of the accelerator, sweep system, analyzer, and control system is described. Four pairs of sweep plates are positioned in both primary and secondary beamlines to actively control the beam trajectory, where the poloidal sweepers require a maximum of 15 kV voltages to be applied. A parallel-plate energy analyzer with multi-slits is supplied by 100 kV high voltage for the electric potential measurement. The signal intensity is also evaluated to be hundreds of nA levels, 5 × 10 7 V/A amplifiers are therefore designed. Software is also developed to include the data acquisition as well as the control and monitoring of HIBP subsystems.